Activation of telomerase by TA-65 enhances immunity and reduces inflammation post myocardial infarction: original article - Bawamia, Bilal; Spray, Luke; Wangsaputra, Vincent K.; Bennaceur, Karim; Vahabi, Sharareh; Stellos, Konstantinos; Kharatikoopaei, Ehsan; Ogundimu, Emmanuel; Gale, Chris P.; Keavney, Bernard; Maier, Rebecca; Hancock, Helen; et al. (GeroScience, 2023)
Myocardial infarction (MI) accelerates immune ageing characterised by lymphopenia, expansion of terminally differentiated CD8+ T-lymphocytes (CD8+ TEMRA) and inflammation. Pre-clinical data showed that TA-65, an oral telomerase activator, reduced immune ageing and inflammation after MI. We conducted a double blinded randomised controlled pilot trial evaluating the use of TA-65 to reduce immune cell ageing in patients following MI. Ninety MI patients aged over 65 years were randomised to either TA-65 (16 mg daily) or placebo for 12 months. Peripheral blood leucocytes were analysed by flow cytometry. The pre-defined primary endpoint was the proportion of CD8+ T-lymphocytes which were CD8+ TEMRA after 12 months. Secondary outcomes included high-sensitivity C-reactive protein (hsCRP) levels. Median age of participants was 71 years. Proportions of CD8+ TEMRA did not differ after 12 months between treatment groups. There was a significant increase in mean total lymphocyte count in the TA-65 group after 12 months (estimated treatment effect: + 285 cells/μl (95% CI: 117-452 cells/ μ l, p < 0.004), driven by significant increases from baseline in CD3+, CD4+, and CD8+ T-lymphocytes, B-lymphocytes and natural killer cells. No increase in lymphocyte populations was seen in the placebo group. At 12 months, hsCRP was 62% lower in the TA-65 group compared to placebo (1.1 vs. 2.9 mg/L). Patients in the TA-65 arm experienced significantly fewer adverse events (130 vs. 185, p = 0.002). TA-65 did not alter CD8+ TEMRA but increased all major lymphocyte subsets and reduced hsCRP in elderly patients with MI after 12 months.